Thermodynamic and kinetic aspects of the solvent-free liquid–liquid synthesis of tailor-made glyceride esters. (1st February 2023) - Santos, Maricel; Velez, Alexis; Abburra, Rogelio; Magario, Ivana
Highlights: Monoglycerides formation was favored at lower temperature using enzymatic catalysis. Lower mutual solubility between reactants favored monoglycerides formation. Activity-based reaction rate is preferred for kinetic parameters calculation. Activity-based equilibrium constants are provided. Abstract: Direct esterification between glycerol and carboxylic acids allows the design of different glycerides according to predetermined applications. Five carboxylic acids (caprylic, capric, lauric, stearic and oleic) which formed a bi-phasic system with glycerol were tested for esterification in a 1:1 M proportion. Two strategies were pursued: on one hand, homogeneous acid catalysis using sulfuric acid or p-toluenesulfonic acid at 100 °C and on the other hand, reactions catalyzed by immobilized lipase B from Candida antarctica at 65 °C. The selectivity and yield for MG was higher at lower temperature and with the use of the enzyme. Lauric acid was the carboxylic acid with the higher yield and selectivity to MG despite the catalyst used. The decrease in the mutual solubility between the carboxylic acid and glycerol seems to favor MG formation. The rate of reaction decreased with the increase in the molecular weight of the carboxylic acid used and the introduction of one unsaturation. From caprylic to lauric acid, the catalyst performance was: p-toluenesulfonic acid > lipase > sulfuric acid whereas for stearic and oleic acids the lipase was superior. Reactant accumulation at the interface is proposed to explain these results. The thermodynamic UNIFAC model was applied to calculate the initial activity coefficients and molar fractions in each phase. It was demonstrated that the thermodynamic activity of the species is a more convenient representation of the effective concentration for kinetic description of a liquid–liquid system. The equilibrium constant of lipase reaction was calculated with an expression based on the activity of compounds. The equilibrium constant for diglycerides formation decreased with the carbon chain length.